2020
DOI: 10.21203/rs.3.rs-62260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Empowered Work Environments on the Psychological Experiences of Nursing Assistants During COVID-19: A Qualitative Study

Abstract: Background: Nursing Assistants (NA) who feel empowered tend to perform their duties better, have higher morale and job satisfaction, and are less likely to leave their jobs. Organizational empowerment practices in hospitals likely shape the psychological experiences of empowerment among these personnel; however, little is known about this relationship.Objective: We used qualitative inquiry to explore the relationship between organizational empowerment structural components and feelings of psychological empower… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 14 publications
(17 reference statements)
1
17
0
4
Order By: Relevance
“…Outro ponto influente que causou a insatisfação do processo de trabalho do enfermeiro no início da pandemia foi à falta de informações fornecidas, influenciando os sentimentos de medo, falta de preparação, autonomia e competência. Travers et al (2020), compara esses sentimentos sendo semelhantes em outras crises de saúde públicas que surgiram como novas e sem precedentes, a exemplo da epidemia de AIDS dos anos 1980. Wuneh et al (2021), por sua vez, revela que mesmo os profissionais tendo conhecimento sobre as medidas de prevenção e controle da COVID-19, eles tinham percepções negativas sobre a doença e não estavam satisfeitos com seu trabalho atual.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Outro ponto influente que causou a insatisfação do processo de trabalho do enfermeiro no início da pandemia foi à falta de informações fornecidas, influenciando os sentimentos de medo, falta de preparação, autonomia e competência. Travers et al (2020), compara esses sentimentos sendo semelhantes em outras crises de saúde públicas que surgiram como novas e sem precedentes, a exemplo da epidemia de AIDS dos anos 1980. Wuneh et al (2021), por sua vez, revela que mesmo os profissionais tendo conhecimento sobre as medidas de prevenção e controle da COVID-19, eles tinham percepções negativas sobre a doença e não estavam satisfeitos com seu trabalho atual.…”
Section: Resultsunclassified
“…É abordado também que os enfermeiros trabalham sua vulnerabilidade usando pontos fortes, como valores pessoais, sentimento de esperança no combate a pandemia, crenças, juntamente com suas habilidades profissionais no ambiente de trabalho e assim tornar mais propensos a permanecer na força de trabalho. De acordo com Travers et al (2020), o gerenciamento e a capacitação dos enfermeiros durante a pandemia são essenciais para melhorar sua satisfação no trabalho, desempenho, moral e retenção. É preciso trabalhar as experiências psicológicas de empoderamento e isso inclui: transmitir informações para aliviar os medos; capacitá-los e permitir que sejam autônomos, inovadores e pró-ativos quando houver novas oportunidades no local de trabalho; garantir o acesso aos recursos; fornecer apoio; reconhecer suas contribuições; permitir apoio espiritual também é importante.…”
Section: Resultsunclassified
“…They do not readily sit in meetings in which their presence is critical (eg, huddles or resident and patient care discussions), and ways for them to contribute to resident care plans are often not standardized. 9 The intention may be for nursing assistants to be a part of these spaces, however, the nursing assistants being classified as too busy is often used as an excuse for not extending the invitation. 9 , 10 When nursing assistants are not invited to the party, they are not held accountable for IPC efforts in ways that can help them appreciate their potential impact in this area.…”
Section: What Is Diversity Equity and Inclusion And How Does It Relat...mentioning
confidence: 99%
“… 9 The intention may be for nursing assistants to be a part of these spaces, however, the nursing assistants being classified as too busy is often used as an excuse for not extending the invitation. 9 , 10 When nursing assistants are not invited to the party, they are not held accountable for IPC efforts in ways that can help them appreciate their potential impact in this area. 10 During the pandemic, specifically, many decisions around COVID-19 were often made without the input of nursing assistants.…”
Section: What Is Diversity Equity and Inclusion And How Does It Relat...mentioning
confidence: 99%
“…Relationship between variables affecting anxiety and resilience using linear regression comparison in terms of resilience and anxiety between nurses working in COVID-19 wards and nurses working in other wards: a descriptive cross-sectional study in southern Iran Thus, nursing administrators must employ effective strategies, e.g. resilience training and stress management, to decrease nurses' anxiety and exposure to occupational injuries and enhance their resilience Travers et al (2020). reported that the psychological empowerment of nurses in COVID-19 hospital wards lowers their occupational anxiety and improves their resilience skills.…”
mentioning
confidence: 99%